Effect of Hygromycin B Antibiotic Produced by Streptomyces Isolates on some Pathogenic Bacteria - Al-Shaibani, Abdul Wahid B; Jabbar, Rabah N; Sharba, Zahraa Abdulmunim (Al-Nahrain Journal of Science, 2018)
To select the most efficient isolate in production of the antimicrobial agent Hygomycin B, 53 Streptomyces soil isolates were examined. DNA of these isolates was extracted and screened by Polymerase Chain Reaction (PCR) technique for the presence of Hygomycin B gene which is responsible for production of such agent. Among the 53 isolates, only three gave positive results for the existence of this gene when the three isolates were evaluated for their antimicrobial activity, an isolate symbolled Streptomyces “10cm/35pigment” was the superior by giving the highest activity against four of the seven test microorganisms (Proteus mirabilis, Staph. aureus, Sal. typhi and Sacch. cerevisiae) used in the study. Their recorded inhibition zone diameters were 70, 55, 33 and 38 mm, respectively. After subjection of the superior isolate to the cultural, microscopic and biochemical characterization, it was identified as Streptomyces hygroscopicus.